Holistic Generative Modeling Process for HBIM - Banfi, Fabrizio (Politecnico di Milano, 2019)
In recent years, innovation in the Digital Cultural Heritage (DCH) domain has been supported by the development of modern 3D survey tools able to transmit morphological characteristics of heritage buildings, revealing their uniqueness. Unfortunately, the intricate reality of the built heritage and the growing need to represent the actual geometry using 3D models collide with the paradigms of complexity and accuracy and opening an operative perspective for preservation, restoration and conservation. The absence of 3D objects corresponding to complex historical elements in BIM libraries requires the creation of three-dimensional objects through a restricted set of modeling commands, requiring a huge manual effort, long processing times and significant information loss during the generative process. Generative modeling has been identified as one of the barriers for the generation of a heritage building in BIM software (HBIM). Against this backdrop, this thesis proposes a Modeling Management Information System (MMIS) characterised by novel grades of generations (GOG), accuracy (GOA) and information (GOI) oriented to improve the modeling and information sharing of complex elements from point cloud data (Terrestrial laser scanning TLS, Digital Photogrammetry DP), and to face the paradigm of complexity (built heritage and its architectural and structural elements) against the regularity of BIM libraries (simple geometric shapes for new buildings). Once the specific modeling requirements have been determined, an add-in has been developed for Autodesk Revit (tech solution) in order to support users in generating a proper Scan-to-BIM model in a single workflow (cost-effectiveness), improving the cooperation and interoperability among different actors and scientific disciplines (coworking). The generative model concept aims to migrate to the generative modeling in the HBIM parametrization, thus allowing it to tackle a full interoperability , switching to different environments behind BIM such as the design, the restoration, the Finite Element Analysis (FEA), the Construction Site Information Modelling (CoSIM), the Facility Management (FM) and the Mixed reality (Virtual and augmented reality VR/AR), becoming a useful link in of a long chain of interconnected users, from specialists, to tourists and ordinary citizens (holistic impact).
Keywords: HBIM; Cultural Heritage